Democratizing from within: British elites and the expansion of the franchise - Chitralekha Basu; Carles Boix; Sonia Giurumescu; Paulo Serôdio (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We develop a theory of democratization that integrates both electoral calculations and economic incentives to explain the institutional choices of political actors. Left-leaning (liberal) politicians, who, given their location in the policy space, are more likely to receive the support of newly enfranchised voters, favor a broader franchise than conservative ones. Their preferences are conditional on the distributional effects of the franchise: when inequality is higher, policymakers are more reluctant to expand it because it is harder to reconcile the policy demands of existing and new voters. We evaluate this theory by estimating the franchise preferences of British MPs based on their votes on franchise-related parliamentary divisions between 1830 and 1918, and linking these preferences to their personal and constituency characteristics. Our results, which are consistent with our theory, show that declining inequality and the First World War were crucial factors in the democratization of Britain in this period.
Keywords: D72; N43; 330; Democratization; Franchise extension; British political development; Electoral competition